2021
DOI: 10.20524/aog.2021.0571
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-acetylcysteine in non-acetaminophen-related acute liver failure: an updated meta-analysis and systematic review

Abstract: Background The American Association for the Study of Liver Diseases recommends that N-acetylcysteine (NAC) may be beneficial in non-acetaminophen-related drug-induced liver injury. A subsequent review and analysis reported the current evidence to be inconclusive. Herein, we present an updated review and meta-analysis. Methods We evaluated prospective, retrospective and randomized controlled trials that compared outcomes in patients of all ages with acute liver failure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…The administration of intravenous NAC in patients with acute liver failure not induced by paracetamol shortly after admission reduces mortality and the need for liver transplantation, in addition to reduced encephalopathy, hospitalization, admission to the intensive care unit and failure of other organs [ 157 ]. Corroborating these data, a recent meta-analysis also concluded that NAC improves survival, transplant-free survival, post-transplant survival and length of hospital stay for patients with acute liver failure unrelated to paracetamol [ 158 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…The administration of intravenous NAC in patients with acute liver failure not induced by paracetamol shortly after admission reduces mortality and the need for liver transplantation, in addition to reduced encephalopathy, hospitalization, admission to the intensive care unit and failure of other organs [ 157 ]. Corroborating these data, a recent meta-analysis also concluded that NAC improves survival, transplant-free survival, post-transplant survival and length of hospital stay for patients with acute liver failure unrelated to paracetamol [ 158 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Pharmacological interventions such as supplementation of antioxidants to reduce the oxidative stress have been explored to minimize the risk of liver damage 8 10 . The FDA approved drug N-acetylcysteine (NAC) is an antioxidant and glutathione inducer indicated for the treatment of fulminant liver failure due to paracetamol overdose 11 . NAC has also been utilized for ameliorating hepatocyte damage in IRI experimental models, while more clinic outcome data is required before the routine use of NAC 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…2,6 In a recent metaanalysis of 7 studies, the use of NAC was associated with improvement in OS, TFS and PTS in patients with NA-ALF. 7 There was significant reduction in duration of hospital stay. In this meta-analysis, most common etiology of ALF was acute viral hepatitis.…”
mentioning
confidence: 89%
“…11 A systemic review comparing oral and intravenous NAC showed similar level of hepatotoxicity in rats with acetaminophen overdose and route of dosing didn't make much difference. 7 One fears that oral NAC may have impaired absorption in, poor tolerance (due to nausea and vomiting), delayed gastric emptying and intestinal failure in setting of ALF. 11 A prospective study which included the sick patients with ALF failed to show any significant benefit (in terms of OS and duration of hospital stay) using NAC by oral route.…”
mentioning
confidence: 99%
See 1 more Smart Citation